Fachliches Lernen im bilingualen Geographieunterricht - Kroß, Eberhard (Journal of Geography Education, 2007)
Bilingual teaching is gaining importance in German schools and a didactic of bilingual teaching in geography is being created. The teaching of domain specific vocabulary is a key issue. Will this happen according to the requirements of language teaching elaborated by linguistics, or will it follow independent principles of its own? The proposal made here is to work according to the principles of fundamental learning formulated by Klafki. The use of blackboard drawings to illustrate and explain domain specific concepts and their basic vocabulary is a central feature, thus making use of cognitive models such as the mental lexicon developed by Aitchison, the dual-coding approach suggested by Paivo as well as the levels of processing discussed by Craik and Lockhart. Four examples are given, one showing the joint use of foreign vocabulary and German equivalents. The conclusion is that a well structured blackboard image would not only facilitate the learning of geography in a foreign language but that it would also enhance the comprehension of the basic concepts in the discipline. Thus the problem of the additional time involved in bilingual teaching could turn out to be a great advantage. This may help to explain the paradox that pupils taught a specific domain in a foreign language can, over the longer term, do as well as those instructed in their mother tongue.